Pozyskiwanie funduszy unijnych w gminach o zróżnicowanym poziomie kapitału ludzkiego władz samorządowych - Kusto, Barbara (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2011)
The aim of this study is to present the significance of human capital in activities undertaken by local government authorities in order to acquire EU funds. The study involved all municipalities of the Swietokrzyskie Province (101), excluding the City of Kielce with county rights. The study focuses on the determination of the human capital level of local government authorities in Swietokrzyskie Province and presents an assessment of how human capital contributes to the degree of use of financial means that were acquired by municipalities from EU funds in 2007–2010. Human capital quality of local government authorities was found to correlate with the number and value of EU projects ventured by municipalities.